1980
DOI: 10.1530/jrf.0.0590163
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt decrease in daylength and short-term changes in the plasma concentrations of FSH, LH and prolactin in anoestrous ewes

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 15 publications
5
34
1
Order By: Relevance
“…Twenty-two days after a four hour reduction in light the prolactin levels in both control and melatonin treated ewes decreased to 5 % of the initial levels. These results confirmed in goats that one of the earliest physiological responses to short daylength was a precipitous drop in plasma prolactin (Walton et al, 1980) and that showed that exogenous melatonin could replicate this response.…”
Section: Introductionsupporting
confidence: 77%
“…Twenty-two days after a four hour reduction in light the prolactin levels in both control and melatonin treated ewes decreased to 5 % of the initial levels. These results confirmed in goats that one of the earliest physiological responses to short daylength was a precipitous drop in plasma prolactin (Walton et al, 1980) and that showed that exogenous melatonin could replicate this response.…”
Section: Introductionsupporting
confidence: 77%
“…In sheep, the pattern of circadian prolactin secretion varies during the year. In spring, a biphasic rhythm of prolactin secretion is observed, with highest levels before noon and in the evening [10, 11, 12]. Lowest levels occur before night-time.…”
Section: Introductionmentioning
confidence: 99%
“…2 h before lights off). Several other studies in pregnant and non-pregnant sheep have reported a similar 'lights off' or 'dusk' peak in prolactin concentrations (Brown & Forbes, 1980;Brinklow & Forbes, 1984;McMillen et al 1987McMillen et al , 1991Poulton, English, Symon & Arendt, 1989;Walton, Evins, Fitzgerald & Cunningham, 1989). The diurnal prolactin rhythm in the ewe persists after pinealectomy or after sympathetic denervation of the pineal gland which suggests that the presence of the pineal gland is not required for the generation of this rhythm (Lincoln, 1979;Brown & Forbes, 1980;Brinklow & Forbes, 1984;Poulton et al 1989;Maxwell, Rintoul, Foldes, Downing, Scaramuzzi & Carter, 1989;McMillen et al 1991).…”
Section: Prolactinmentioning
confidence: 80%